Sustaining tropical timber trees in production forests of Asia - ensuring their genetic viability - Jalonen, R.; Hong, L.T.; Lee, S.L.; Loo, J.; Snook, Laura K.; Bioversity International; Forest Research Institute of Malaysia (2014)
Sustainable timber production in approximately 400 million hectares of production forests in the tropics would be enhanced by incorporating genetic conservation measures in their management. This factsheet, based on a scientific review, explains why tropical Asian timber species are particularly vulnerable to logging and habitat fragmentation and what policymakers and forest managers can do to maintain productivity and resilience of timber trees in Asian production forests.